INTEGRASI PENDEKATAN HISTORIS DAN SOSIOLOGIS DALAM PENAFSIRAN AYAT-AYAT MODERASI BERAGAMA : Studi Kasus pada Pesantren di Jawa Timur - Fuad Ngainul Yaqin (Jurnal Studi Pesantren, 2024)
Religious moderation is a key national agenda item included in the 2020–2024 National Medium-Term Development Plan (RPJMN) and is aligned with the Qur’anic value of wasathiyyah (moderation). As centers of traditional Islamic education, pesantren play a strategic role in instilling the values of religious moderation through Qur’anic exegesis instruction. However, teaching methods that remain normative and based on classical texts require more adaptive and contextual approaches to remain relevant to contemporary challenges.This study aims to analyze the integration of historical and sociological approaches in interpreting Qur’anic verses on religious moderation in three major pesantren in East Java: Pondok Pesantren Lirboyo Kediri, Pondok Pesantren Tebuireng Jombang, and Pondok Pesantren Sidogiri Pasuruan. Using a qualitative-descriptive method, data were collected through in-depth interviews, participatory observations, and document analysis. The findings show that integrating the two approaches helps students (santri) understand the historical context of revelation while linking it to the social realities of contemporary society. This model strengthens students’ understanding of religious moderation both textually and contextually, enhances the relevance of Qur’anic exegesis to contemporary social issues, and encourages curriculum changes toward greater openness. Nevertheless, several challenges were identified, including limited access to contemporary tafsir literature, resistance from some teachers, and time constraints within the curriculum. The study concludes that integrating historical and sociological approaches produces a contextual model of Qur’anic interpretation on religious moderation that is adaptive and responsive to current needs. It is recommended that future researchers expand the scope of study to include modern pesantren or those outside East Java and explore the use of digital technology to support the wider implementation of this interpretive model.